The adenomatoid odontogenic tumour: an update of selected issues - Philipsen H. (2017)
© 2016 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd The aim of this update was to present the recent notable progress within remaining questions relating to the adenomatoid odontogenic tumour (AOT). Selected issues that were studied included the following: (i) AOT history and terminology, (ii) the so-called peripheral AOT, (iii) AOT and the gubernaculum dentis and (iv) the so-called adenomatoid odontogenic cyst (AOC). The earliest irrefutable European case of AOT was described in 1915 by Harbitz as ‘cystic adamantoma’. Recently, Ide et al. have traced two Japanese cases with irrefutable proof described by Nakayama in 1903. The so-called peripheral (gingival) variant of AOT seems to cover a dual pathogenesis, both an ‘erupted intraosseous’ and an ‘extraosseous’ (gingival) one. In 1992, we theorized that the generally unnoticed gubernaculum dentis (cord and canal) seems to be involved in the development of AOT. Ide et al. have concluded that the dental lamina in the gubernacular cord seems to be an embryonic source of the vast majority of AOTs. The suggestion by Marx and Stern to change the nomenclature of AOT to adenomatoid odontogenic cyst (AOC) is critically discussed. The present authors agree on the background of the work of several groups of researchers and WHO/IARC classifications that the biology of the follicular variant of AOT is already fully explained and does not make room for any change in diagnostic terms. Further, there is no reason to change terminology in this case where improvements or conditions to better clinical management are not an issue.